Mare's war - Davis, Tanita S. (New York : Alfred A. Knopf, 2009)
Teens Octavia and Tali learn about strength, independence, and courage when they are forced to take a car trip with their grandmother, who tells about growing up Black in 1940s Alabama and serving in Europe during World War II as a member of the Women's Army Corps.
A Junior Library Guild selection
Keywords: United States. -- Army. -- Women's Army Corps -- Juvenile fiction; United States. -- Army. -- Women's Army Corps -- Fiction; Automobile travel -- Juvenile fiction; Grandmothers -- Juvenile fiction; African Americans -- Juvenile fiction; World War, 1939-1945 -- Juvenile fiction; Sisters -- Juvenile fiction; Families -- Alabama -- Juvenile fiction; Automobile travel -- Fiction; Grandmothers -- Fiction; African Americans -- Fiction; World War, 1939-1945 -- Fiction; Sisters -- Fiction; Family life -- Alabama -- Fiction; Alabama -- History -- 1819-1950 -- Juvenile fiction; Alabama -- History -- 1819-1950 -- Fiction